Understanding fall risk for older adults with cancer: An evaluation of experts' perceptions. Issue 2 (March 2020) - Covington, Kelley R.; Atler, Karen E.; Schmid, Arlene A.; Pergolotti, Mackenzi
Abstract: Objective: Older adults with cancer have elevated risk of falling. However, cancer-specific fall risk factors are not well understood. Methods: A pragmatic, qualitative study utilized semi-structured interviews to investigate expert's perceptions of fall risk for older adults with cancer. Interview questions were guided by the International Classification of Functioning and Disability (ICF) constructs and the Cancer Aging Research Group's model of fall risk factors. Themes were identified deductively from interview transcriptions. Transcripts were coded using Nvivo software. Results: Ten multidisciplinary experts participated ( n = 5 clinical, n = 5 research). Two themes in fall risk factors emerged from interview data: 1) cancer-specific factors aligned with each ICF construct: body function and structures (BF&S), activity and participation (A&P), personal and environmental factors; and 2) a cycle among factors. Experts described that treatment-related limitations in A&P produced or exacerbated impairments in BF&S (physical and mental), leading to falls and further limitations in A&P. Personal and environmental factors influencing this cycle included: cancer-related distress, social support, and perceptions of aging and treatment. Conclusion: Experts identified a cycle among cancer-specific fall risk factors for older adults and emphasized the importance of a "holistic" view of the patient to evaluate fall risk. Cancer-related distress, social support and expectations of aging and treatment may influence the cycle between risk factors, with potential negative or protective effects. Future prospective, longitudinal implementation of geriatric assessments and analysis of data may inform risk factors and relationships among factors. Patient interviews could further inform the understanding of fall risk for older adults with cancer.